The Challenges and Rewards of Co-Chairing a Department: Lessons Learned from Leaders in the Middle - Laura Trujillo-Jenks; gina Anderson (Academic Chairpersons Conference Proceedings, 2022)
Newly appointed Department Chairs are often on their own to learn “on the job” the knowledge and skills they will need to succeed. One way to mitigate the challenges of this high-stakes approach is to identify a second leader who can serve in the role of mentor, coach or Co-Chair alongside the new Chair. The Co-Chair may be a leader who has served as a Department Chair in the past and/or who is serving in another middle-management position such as a Chair from a different department, Director, or Associate Dean. During a time of tremendous change and uncertainty, the Co-Chair may provide additional support and stability while also helping the new Chair understand and practice their new roles and responsibilities. During this session, a Chair and Co-Chair will share their experiences, and session attendees will be invited to participate in an interactive discussion.
Keywords: Mentoring; Co-Chair; Professional Development